Sexual dimorphism in the dioecious willow Salix purpurea. Issue 8 (18th August 2021) - Gouker, Fred E.; Carlson, Craig H.; Zou, Junzhu; Evans, Luke; Crowell, Chase R.; Smart, Christine D.; DiFazio, Stephen P.; Smart, Lawrence B.
Abstract: Premise: The evolution of sex chromosomes is driven by sexual dimorphism, yet it can be challenging to document sexually dimorphic traits in dioecious plant species. At the genetic level, sexual dimorphism can be identified through sequence variation between females and males associated with sexually antagonistic traits and different fitness optima. This study aims to examine sexual dimorphism for 26 traits in three populations of Salix purpurea (a diversity panel and F1 and F2 populations) and determine the effect of the traits on biomass yield, a key trait in Salix bioenergy crops across multiple years, locations, and under manipulated growth conditions. Methods: Sexual dimorphism was evaluated for morphological, phenological, physiological, and wood composition traits in a diversity panel of unrelated S. purpurea accessions and in full‐sib F1 and F2 families produced through controlled cross pollinations and grown in replicated field trials. Results: We observed sexual dimorphism in the timing of development for several traits that were highly predictive of biomass yield across three populations of S. purpurea . Across all populations and years surveyed, males had significantly shallower branching angle. Male plants highly predictive of biomass yield across three populations of S. purpurea also accumulated more nitrogen under fertilizer amendment as measured by SPAD in the diversity panel and had greater susceptibility to the rust fungus Melampsora americana in the F2 family. Allometric modelling of biomass yield showed an effect of sex and of location on the interaction between yield and stem height. Conclusions: These results provide evidence of sexual dimorphism for certain traits in S. purpurea that may be involved in sex chromosome evolution.